2019
DOI: 10.3390/nu11061343
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Modulates the Microenvironment of Glioblastoma Multiforme by Targeting Sirtuin 1

Abstract: Natural products have historically been regarded as an important resource of therapeutic agents. Resveratrol and melatonin have been shown to increase SIRT1 activity and stimulate deacetylation. Glioblastoma multiforme (GBM) is the deadliest of malignant types of tumor in the central nervous system (CNS) and their biological features make treatment difficult. In the glioma microenvironment, infiltrating immune cells has been shown to possess beneficial effects for tumor progression. We analyzed SIRT1, CCL2, VC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 88 publications
(92 reference statements)
2
26
0
Order By: Relevance
“…The procedure of the monocyte-binding assay was described previously [76,77]. Briefly, human monocyte THP-1 cells were incubated with BCECF/AM (2 ,7 -bis-(2-carboxyethyl)-5-(and-6)carboxyfluorescein) and 0.1 µg fluorescent dye of in RPMI-1640 medium in an incubator for 1 h. GBM cells were treated with CHC or were transfected with short hairpin or wild-type MCT4 for the different time periods.…”
Section: Monocyte-binding Assaymentioning
confidence: 99%
“…The procedure of the monocyte-binding assay was described previously [76,77]. Briefly, human monocyte THP-1 cells were incubated with BCECF/AM (2 ,7 -bis-(2-carboxyethyl)-5-(and-6)carboxyfluorescein) and 0.1 µg fluorescent dye of in RPMI-1640 medium in an incubator for 1 h. GBM cells were treated with CHC or were transfected with short hairpin or wild-type MCT4 for the different time periods.…”
Section: Monocyte-binding Assaymentioning
confidence: 99%
“…On the one hand, SIRT1 knockdown significantly inhibited glioma cell proliferation, migration, invasion, promoted its apoptosis and potentiated TMZ toxicity (39)(40)(41). On the other hand, the expression of SIRT1 in GBM is significantly lower than normal brain tissue (42,43). Up-regulation of SIRT1 by genetic modification or treatment of melatonin significantly attenuated the adhesion molecular VCAM-1 and ICAM-1 expression in GBM, which modulated the monocytes interaction with GBM (43).…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, the expression of SIRT1 in GBM is significantly lower than normal brain tissue (42,43). Up-regulation of SIRT1 by genetic modification or treatment of melatonin significantly attenuated the adhesion molecular VCAM-1 and ICAM-1 expression in GBM, which modulated the monocytes interaction with GBM (43). SIRT1 activator SRT2183 suppresses glioma cell growth and destroyed neurospheres in vitro (44).…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of monocyte-related tumor-promotion effects in GBM could be a potentially useful antineoplastic strategy. With this in mind, Lai et al [73] reported that in vitro melatonin supplementation reduced monocyte adhesion molecules, as well as monocyte chemoattractant chemokine CCL2 expression in GBM, consequently attenuating monocyte recruitment and activity. Importantly, Lai et al [73] also observed that administration of melatonin increased the expression of sirtuin 1, which, in turn, reduced the expression of monocyte adhesion molecules.…”
Section: In Vitro Evidence Of Melatonin Effects Against Glioblastomamentioning
confidence: 99%